Balancing the rights of the coastal state in its exclusive economic zone and freedom of navigation of other states: an analysis of the practice of Asian countries - Hamid, Abdul Ghafur@Khin Maung Sein (2007)
The UN Convention on the Law of the sea creates a delicate balance between the rights of the coastal State and those of other States in the EEZ. The present paper argues that although the balance created by the Convention is impressive, its application is not easy. As national interests are involved, state practice is not exactly in confirmity the Convention. The paper analyses national laws of selected Asian countries and finds that although most of them follow the Convention formula of balancing, some are clearly at variance with it and some are controversial. The paper concludes that states parties to UNCLOS are obliged to fulfil in good faith the obligations under the Convention and that the delicate balance between coastal and user states rights can be achieved in practice only by menas of mutual understanding and sincere negotiations.